HIGHLIGHTING WOMEN'S EQUALITY AND INJUSTICE IN LITERATURE - Nurweni Saptawuryandari (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Equality is the same thinking between men and women to hold fast to their lives. In fact, equality in feminism is related to gender equality between men and women who have the same position in any case, one of which is work. Therefore, this study aims to reveal (1) how equality and injustice against women are reflected in literary works, especially the novel "Perempuan Panggung" and the short story "Laila" and (2) how to deal with equality and injustice against women in the novel "Perempuan Panggung" and the short story "Laila". This research is a qualitative research using a feminism approach. The data sources of this research are the novel entitled "Perempuan Panggung" by Iman Budhi Santosa and the short story "Laila" by Putu Wijaya. Data collection techniques using literature study. The results show that the inequality and injustice experienced by women is the lack of equality and justice in attitudes, actions, opinions, and work.